2011
DOI: 10.1063/1.3559269
|View full text |Cite
|
Sign up to set email alerts
|

Tuning optical modes in slab photonic crystal by atomic layer deposition and laser-assisted oxidation

Abstract: The authors experimentally investigate the effects of atomic layer deposition (ALD) and laser-assisted oxidation on the optical modes in GaAs L3 photonic crystal air-bridge cavities, using layers of InAs quantum dots as internal light source. Four distinct optical mode peaks are observed in the photonic bandgap and they show different wavelength-redshifts (0–6.5 nm) as the photonic crystal surface is coated with an Al2O3 layer (0–5.4 nm thick). Numerical finite-difference time-domain (FDTD) simulations can wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“… when average power was raised. The conformal growth of Al 2 O 3 effectively prevents oxidation, as already shown on photonic crystal structures . We confirm that ALD‐coated samples are remarkably stable even under exposure to intense optical flux.…”
Section: Ald Passivationsupporting
confidence: 83%
“… when average power was raised. The conformal growth of Al 2 O 3 effectively prevents oxidation, as already shown on photonic crystal structures . We confirm that ALD‐coated samples are remarkably stable even under exposure to intense optical flux.…”
Section: Ald Passivationsupporting
confidence: 83%
“…Since 2003, photonic crystals have been intensively investigated for their potential to confine, as well as to guide, light. Many researchers have demonstrated that ALD allows rapid and flexible fabrication of photonic crystals, and opals …”
Section: Development Of Ald In the Field Of Optical Microcavitiesmentioning
confidence: 99%
“…The ALD approach for self‐assembled 3D photonic crystals and opal structures has been extended to include a broad variety of materials. Ta 3 N 5 , ZnO, GaAs, Al 2 O 3 , TiO 2 , and ZnS have all been used to produce multilayer inverse opal structures. The wavelength of the peak Bragg reflection was observed to shift to progressively longer wavelengths versus the ALD thickness of inorganic thin films .…”
Section: Development Of Ald In the Field Of Optical Microcavitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This method relies on atomic layer deposition (ALD) to infiltrate the waveguide structures with thin layers of dielectric. While ALD has previously been used to adjust geometric parameters of bulk photonic crystals [14] and to tune optical modes in two-dimensional photonic crystal slabs [15,16], this is the first time it is successfully employed to induce systematic changes in the optical properties of a 3D PBG waveguide. In principle the method is not limited to the waveguides considered here but it can be applied to any 3D photonic crystal defect structure suitable for infiltration, including point-defect cavities.…”
Section: Introductionmentioning
confidence: 99%